Literature Review: The Effect of E-Procurement Role, Procurement Ethics, and Human Resources Quality on Fraud Prevention in Goods/Services Procurement - Rachmawati Yuslina; Kuntadi, Cris; Yeni Fahrinda (Dinasti International Journal of Digital Business Management, 2023)
In the process of procurement of goods/services there is still a gap to commit fraud, because there are still considerable fraudulent practices in the procurement of goods/services. This article aims to propose a conceptual model of the factors that influence the prevention of fraud in the procurement of goods/services. Fraud that occurs in the public and private sectors is one of the causes of state or company finances swelling, even programs that have been planned by the government have many problems in the implementation process. This article reviews the influence of the role of E-Procurement, Procurement Ethics, and the Quality of Human Resources on the Prevention of Fraud in the Procurement of goods/services. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results are that E-Procurement affects the prevention of fraud in the procurement of goods/services; Procurement Ethics affects the prevention of fraud in the procurement of goods/services; and the Quality of Human Resources affects the prevention of fraud in the procurement of goods/services.